Body image pada mahasiswi dimasa pandemi: Bagaimana peranan laxative abuse? (SUKMA : Jurnal Penelitian Psikologi, 2021)
The existence of a pandemic phenomenon forces female students to feel less moving and even exercise, so that they feel their weight gain rapidly due to changes in physical activity that are different from usual. Based on a preliminary study conducted by researchers on 38 UNTAG students, it was found that 33 out of 38 female students admitted to using laxative drugs as an alternative to maintain the perception of body image in order to feel ideal during the pandemic. This study aims to determine the relationship between laxative abuse and body image among UNTAG students during the pandemic. From a population of 771 female students, about 60 female students were taken to become subjects in this study. Taking the subject begins with determining the criteria. The criteria needed in this study were women, UNTAG active students, aged 19-25 years, using laxative drugs. The sampling technique used was purposive sampling technique. Collecting data in this study used body image scale and laxative abuse scale with Product Moment correlation analysis technique which showed a significant positive correlation between laxative abuse variable and body image in UNTAG students. So that there is a positive relationship between Laxative Abuse behavior and body image in female students. The higher the level of Laxative Abuse behavior, the more negative body image in female students.Adanya fenomena pandemi memaksa mahasiswi terpaksa merasa kurang bergerak bahkan berolahraga, sehingga merasa berat badannya bertambah secara cepat karena peruabahan aktifitas fisik yang berbeda dari biasanya. Berdasarkan studi pendahuluan yang dilakukan peneliti terhadap 38 mahasiswi UNTAG, ditemukan bahwa 33 dari 38 mahasiswi mengaku menggunakan obat laxative sebagai alternatif untuk menjaga persepsi body image agar tetap merasa ideal selama masa pandemi. Penelitian ini bertujuan untuk mengetahui hubungan antara laxative abuse dengan body image  pada mahasiswi UNTAG di masa pandemi. Dari populasi yang berjumlah 771 mahasiswi diambil sekitar 60 mahasiswi guna menjadi subyek dalam penelitian ini. Pengambilan subyek diawali dengan menentukan kriteria. Kriteria yang dibutuhkan dalam penelitian ini adalah Wanita, Mahasiswi Aktif UNTAG, Usia 19 - 25 tahun, Menggunakan Obat laxative. Teknik sampling yang digunakan adalah teknik purposive sampling. Pengumpulan data dalam penelitian ini menggunakan skala body image  dan skala laxative abuse dengan teknik analisis korelasi Product Moment yang menunjukkan adanya korelasi positif yang signifikan antara variabel laxative abuse dengan body image pada mahasiswi UNTAG. Sehingga ada hubungan  positif antara perilaku Laxative Abuse  dengan  body image  pada mahasiswi. Semakin tinggi tingkat perilaku Laxative Abuse maka semakin  negative body image pada mahasiswi.